Aplikasi Pendekatan Interdisipliner dalam Studi Hukum Perkawinan: : Studi Kasus Perkawinan di Bawah Umur - ucu, Ardianto (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This paper aims to strengthen the opinion that says the importance of applying a more conical interdisciplinary approach to the study of marriage law and applying an interdisciplinary approach in studying, exploring, understanding, and applying Islamic family law in everyday life. Research using qualitative methods. While the approach used in this study is legal sociology with the theory of legal effectiveness. The results of this study resulted in three conclusions. First, interdisciplinary means collaboration between one science and another in examining a problem, is a unit with its own method. In addition, it is also said that integration between one science and another, so as to form a new science and with new methods. For example, the combination of social and political becomes socio-political, the combination of politics and religion becomes political-religious, the combination of psychology and social becomes social psychology and so on. The need for habituation in using an interdisciplinary approach in studying, understanding and practicing all legal issues, especially those bound by family law. Second, an interdisciplinary approach is one method that is able to answer increasingly complex problems. Besides that, the interdisciplinary approach that is being operated also provides a new perspective in answering existing problems, so that the interdisciplinary approach is expected to become a distinction in the content of family law. And thirdly, in the perspective of legal sociology and legal effectiveness theory, child marriage is still an unresolved social problem, even though Islamic law rules and laws have regulated the age limit for marriage. This was driven by the lack of awareness of the rural community that these regulations were promulgated. So that the practice of underage marriage still often occurs continuously. Sociologically, the occurrence of the practice of underage marriages is motivated by the belief of the community that a child who enters the age of puberty must be married off immediately, in order to avoid greater dangers, such as committing acts that are prohibited by religion (violating religious rules). . Keywords: Application, Interdisciplinary Approach, Marriage Law